Modelagem para cálculo de tensões induzidas por descargas atmosféricas - Fernando Henrique Silveira (2006)
Lightning Induced Voltages are known as one of the most important phenomena capable to cause severe damages to electrical systems and telecommunication networks. Despite the lower severity of their effects in relation to those associated with direct strikes, the probability of occurrence of lightning induced voltages is much more pronounced. This scenario justifies the development of evaluations that aim a better characterization of such phenomenon. The objective of this work is to present a computational model for lightning induced voltages calculations based on electromagnetic field equations. Such model incorporates simultaneously the current distribution along lightning channel and the electromagnetic coupling between line conductors and channel. Furthermore, both stages are automatically computed without the requirement of theoretical assumptions of the behaviour of lightning current distribution or of the electromagnetic interaction between the elements of the analyzed system. The model has physical appeal and reproduces, even in a simplified way, physical features and associated process of the lightning channel. In addition, it can also model conductors in any arbitrary angles, allowing evaluations concerning inclined lightning strokes, tortuosities along the channel and complex line configurations. The main aspects concerning the model application to determine the temporal and spatial current distribution along the channel are described, including the adopted considerations to represent physical features of the channel. Sensitivity analyses to evaluate the effect of several parameters in such distribution are presented. Furthermore, comparison of electromagnetic fields calculated by the model and experimental data are performed, remarking a good agreement between them. Systematic simulations concerning the model application for lightning induced voltages calculations were developed in order to evaluate the role played by the most relevant parameters on the resultant induced voltage. It was also performed comparison of results with other traditional models presented in literature for lightning induced voltages evaluations, as well the comparison with experimental data from lightning induced voltages measurements. The obtained results remarked the reliability of the proposed model. This work also presents the approach to take into account the effect of soil resistivity on lightning induced voltages concerning the modification of the electromagnetic coupling between lightning channel and line conductors. The obtained results remarked very similar behaviour in comparison with other evaluations reported in literature.